Community Service Helps Businesses Development in Creating a Business Model Canvas for the PTL Coffee in South Solok Regency, West Sumatra: Pengabdian Kepada Masyarakat Membantu Usaha Berkembang dalam Pembuatan Business Model Canvas pada Usaha PTL Coffee di Kabupaten Solok Selatan, Sumatera Barat - Wisnubroto, Muhammad Parikesit; Yulianto, Kiki (Universitas Lancang Kuning, 2024)
Community service is a form of activity to transfer and apply knowledge and technology directly to help people's lives improve and develop, including owners of Micro, Small and Medium Enterprises (MSMEs). This community service program was carried out for PTL Coffee MSMEs located in Nagari Lubuk Gadang Selatan, Sangir District, South Solok Regency, West Sumatra Province, with the theme of creating a Business Model Canvas (BMC). This service aimed to find out the right business model for the sustainability of the PTL Coffee. Besides, it is expected that new ideas can be found to support the development of PTL Coffee through analysis of existing businesses. Activities were conducted online through presenting material using Zoom Meetings and offline by visiting PTL Coffee to help make BMC. The discussion during the Zoom Meeting proceeded smoothly, and the attendees appeared excited to listen to the materials delivered. Overall, PTL Coffee was able to compile the nine components of BMC successfully, which allowed it to assess the business's strengths and weaknesses. It also helped PTL Coffee set reasonable and targeted goals for the company's future growth.